2020
DOI: 10.30783/nevsosbilen.659945
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Öğretmen Adaylarinin Tasarruf Değeri̇ne İli̇şki̇n Metafori̇k Algilari

Abstract: Sosyal Bilgiler dersinin insan yaşantısı için önemli olan bilgiyi, beceriyi ve değerleri kazandıran bir ders olması; 2005 ve 2018 yıllarında gerçekleştirilen program değişikliklerinde değer eğitimi konusunun program içinde vurgulanması bu araştırmanın hareket noktasını teşkil etmektedir. Bu araştırmada programa yeni girmiş olan "tasarruf" değeri üzerinde çalışılmış ve öğretmen adaylarının "tasarruf" kavramına ilişkin metaforlarının belirlenmesi amaçlanmıştır.Bu araştırmada, nitel araştırma yöntemine uygun olar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…These findings align with similar results observed in studies examining the value of saving. For instance, Uzunöz et al (2020) discovered that pre-service social studies teachers frequently used metaphors such as piggy bank, money, water, tree, family, mother, minimum wage, faucet, state, raindrop, and time in their perceptions of saving. Similarly, Kıyançiçek (2020), in a study on elementary school students' metaphorical perceptions of the value of saving, found that the most common metaphors created by students included money, water, and recycling.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings align with similar results observed in studies examining the value of saving. For instance, Uzunöz et al (2020) discovered that pre-service social studies teachers frequently used metaphors such as piggy bank, money, water, tree, family, mother, minimum wage, faucet, state, raindrop, and time in their perceptions of saving. Similarly, Kıyançiçek (2020), in a study on elementary school students' metaphorical perceptions of the value of saving, found that the most common metaphors created by students included money, water, and recycling.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
“…For example,Aktepe et al (2020),Bolat (2020),Çakmak et al (2017),Çelik and Doğan-Kahtalı (2022),Kıyançiçek (2020),Şekerci and Doğan (2020),Ünalmış et al (2023),Yalçın and Güleç (2022) examined students' metaphorical perceptions in various disciplines. In addition, Dere (2019),Faiz and Karasu-Avcı (2019),Kartal and Ergün (2022),Öztaş (2020),Pürsün et al (2021),Seyhan (2019),Salur (2023),Torun and Şahin (2023),Uzunöz et al (2020),Yılar et al (…”
mentioning
confidence: 99%
“…Therefore, models and theories can be shaped by examining the perceptions of various target audiences towards the concepts, skills, and values used in educational processes through the metaphors they produce. Metaphor studies conducted on concepts such as social sciences, such as history (Candan & Öztaş, 2017;Er Tuna & Mazman-Budak, 2013;Kantekin, 2018), geography (Aydın, 2010;Çepni, 2013;Durmuş & Baş, 2016;Gökçe, 2016;Kantekin, 2018;Öztürk, 2007;Şahin & Kaya, 2016), social studies/course/teacher (Akça Berk, Gültekin, & Çençen, 2015;Akhan, Kılıçoğlu, & Gedik, 2014;Beldağ & Geçit, 2016;Çelikkaya & Yakar, 2015;Güven & Güven, 2009;Kantekin, 2018;Kuru & Pırnaz, 2020) and some values (Aktepe, Uzunöz, & Sarıçam, 2020;Çelikkaya & Seyhan, 2017;Demirkaya & Çal, 2018;Gömleksiz, Kan, & Öner, 2012;İnel, Urhan, & Ünal, 2018;Kılcan & Akbaba, 2013;Kılcan & Akbaba, 2014;Seyhan, 2020;Ulu Kalın & Koçoğlu, 2017;Uzunöz, Aktepe, & Özağaçhanlı, 2020) within the scope of social studies are important in terms of revealing how the nature of social studies is perceived by different target groups. Additionally, determining the perceptions about the skills in social studies through metaphors will also contribute to the evaluation of social studies in terms of skills.…”
Section: Figure 1 the Basic Communication Modelmentioning
confidence: 99%